Stabilization of Fine Sands Using Polyvinyl Acetate - Gamble, Bruce R. (Canadian Geotechnical Journal, 1971)
Consideration is given to the problems of constructing airfields of the fine surface materials typical of the arctic islands. Preliminary laboratory investigations into the use of a polyvinyl acetate binder as a means of increasing penetration resistance and providing stability against erosion in fine sands are reported. Load–penetration tests indicate that specimens treated by spraying or mixing with dilute polyvinyl acetate have greater penetration resistance and surface strength than comparable untreated specimens. Results depend upon the water content and completeness of curing at testing. Under favorable conditions 100% increases in penetration resistance can be obtained for a material cost of approximately $0.03/ft 2 ($0.32/m 2 ). Work with other polymer treatments less susceptible to water and curing conditions is proceeding.